2017
DOI: 10.1111/aogs.13256
|View full text |Cite
|
Sign up to set email alerts
|

Risk of preterm birth in women with cervical intraepithelial neoplasia grade one: a population‐based cohort study

Abstract: Introduction. In this population-based register study our objective was to explore the association of cervical intraepithelial neoplasia, grade 1 and loop electrosurcigal excision procedure with preterm birth. Material and methods. Our population consisted of 4759 women diagnosed with cervical intraepithelial neoplasia, grade 1 during 1997-2009 and their 3021 subsequent deliveries analyzed by loop electrosurcigal excision procedure and parity. Hospital Discharge Register was used to identify women diagnosed fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 28 publications
(30 reference statements)
0
2
0
Order By: Relevance
“…It suggests that the group contains a high proportion of transient HPV infection and low-grade dysplasia with spontaneous remission. In contrast to high-grade dysplasia, low-grade dysplasia was not associated with an increased risk of PTB [15]. A comparison with patients having an untreated high-grade squamous lesion (HSIL) seemed to be more suitable.…”
Section: Discussionmentioning
confidence: 95%
“…It suggests that the group contains a high proportion of transient HPV infection and low-grade dysplasia with spontaneous remission. In contrast to high-grade dysplasia, low-grade dysplasia was not associated with an increased risk of PTB [15]. A comparison with patients having an untreated high-grade squamous lesion (HSIL) seemed to be more suitable.…”
Section: Discussionmentioning
confidence: 95%
“…Amer-Wahlin et al [13] found that automated CTG interpretation had a higher false-positive rate compared to visual interpretation by experienced clinicians. Therefore, the development of automated CTG interpretation systems should be accompanied by rigorous validation and testing to ensure their accuracy and reliability in clinical practice.…”
Section: Related Workmentioning
confidence: 99%